2021
DOI: 10.1039/d1me00088h
|View full text |Cite
|
Sign up to set email alerts
|

Probing remdesivir nucleotide analogue insertion to SARS-CoV-2 RNA dependent RNA polymerase in viral replication

Abstract: Remdesivir (RDV) prodrug can be metabolized into a triphosphate form nucleotide analogue (RDV-TP) to bind and insert into the active site of viral RNA dependent RNA polymerase (RdRp) to further...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(84 citation statements)
references
References 74 publications
3
78
3
Order By: Relevance
“…For instance, remdesivir is an adenosine analogue with a cyano group attached at the 1′-position of the ribose. Both the experimental and computational studies 7 , 9 , 21 , 27 , 29 , 35 , 37 , 41 45 have demonstrated that remdesivir could inhibit the translocation through a “delayed” mechanism when it appears at the upstream site of the nascent strand. The efficiency of such termination can be gradually reduced by increasing the NTP concentration, and the full-length RNA product can be yielded.…”
mentioning
confidence: 99%
“…For instance, remdesivir is an adenosine analogue with a cyano group attached at the 1′-position of the ribose. Both the experimental and computational studies 7 , 9 , 21 , 27 , 29 , 35 , 37 , 41 45 have demonstrated that remdesivir could inhibit the translocation through a “delayed” mechanism when it appears at the upstream site of the nascent strand. The efficiency of such termination can be gradually reduced by increasing the NTP concentration, and the full-length RNA product can be yielded.…”
mentioning
confidence: 99%
“…The RdRp complex structure was retrieved from the RCSB data bank with PDB ID 7BV2 [8] , which was the closed active site conformation [14] . From this structure, only protein chain A plus two RNA chains (chains P and T) were selected, which was then prepared using the Protein Preparation Wizard of Maestro software [15] using default settings.…”
Section: Methodsmentioning
confidence: 99%
“…The nucleotide addition-inhibition cycle (NAC) consists of several sequential states, i.e., an open active site conformation without NTP substrate binding (S1, PDB ID 6M71) [7] , initial binding mode of NTP substrate (S2), the conformational changes of the active site transition from an open state (S2) to a closed state (S3), the phosphoryl transfer reaction leading to a reaction product (S4, PDB ID 7BV2) [8] , and finally i to i+3 translocation of the primer strand (S5) [9] , [10] , [11] , [12] , [13] . More recently, Romero et al (2021) studied the active-site open state of SARS-CoV-2 RdRp using apo form RdRp (PDB ID 7BTF) for the nucleotide initial binding and an closed active site of the polymerase using a reaction product (PDB ID 7BV2) for the stabilized nucleotide insertion [14] , which were guided by base stacking and base pairing with the template nucleotide, respectively [14] . In this study, we used the reaction product structure (PDB ID 7BV2) as a starting structure for building the initial complex structure of the non-covalent binding step of RTP and its analogues to SARS-CoV-2 RdRp and monitoring their conformational stabilities using molecular dynamics simulations (MDS).…”
Section: Introductionmentioning
confidence: 99%
“…MD simulations have been widely used to understand the acting mechanism of RdRp inhibitors as well as to explore the potential inhibitors since the outbreak of the COVID-19 pandemic. 7 , 12 , 27 , 29 In particular, the “delayed chain termination” mechanism exerted by remdesivir has been investigated by MD simulations, 24 , 26 the results of which have not only well-reproduced the experimental observations that the termination occurs at the upstream site of the nascent strand instead of the active site, but also further elucidated the underlying mechanisms. These previous works have suggested that MD simulations are powerful in elucidating the inhibitory mechanisms of nucleotide analogues.…”
mentioning
confidence: 92%